First comprehensive structural and biophysical analysis of MAPK13 inhibitors targeting DFG-in and DFG-out binding modes - Yurtsever, Zeynep; Patel, Dhara A.; Kober, Daniel L.; Su, Alvin; Miller, Chantel A.; Romero, Arthur G.; Holtzman, Michael J.; Brett, Tom J. (Biochimica et biophysica acta, 2016)
P38 MAP kinases are centrally involved in mediating extracellular signaling in various diseases. While much attention has previously been focused on the ubiquitously expressed family member MAPK14 (p38α), recent studies indicate that family members such as MAPK13 (p38δ) display a more selective cellular and tissue expression and might therefore represent a specific kinase to target in certain diseases. To facilitate the design of potent and specific inhibitors, we present here the structural, biophysical, and functional characterization of two new MAPK13-inhibitor complexes, as well as the first comprehensive structural, biophysical, and functional analysis of MAPK13 complexes with four different inhibitor compounds of greatly varying potency. These inhibitors display IC50 values either in the nanomolar range or micromolar range (>800-fold range). The nanomolar inhibitors exhibit much longer ligand-enzyme complex half-lives compared to the micromolar inhibitors as measured by biolayer interferometry. Crystal structures of the MAPK13 inhibitor complexes reveal that the nanomolar inhibitors engage MAPK13 in the DFG-out binding mode, while the micromolar inhibitors are in the DFG-in mode. Detailed structural and computational docking analyses suggest that this difference in binding mode engagement is driven by conformational restraints imposed by the chemical structure of the inhibitors, and may be fortified by an additional hydrogen bond to MAPK13 in the nanomolar inhibitors. These studies provide a structural basis for understanding the differences in potency exhibited by these inhibitors. They also provide the groundwork for future studies to improve specificity, potency, pharmacodynamics, and pharmacokinetic properties. [Display omitted] •First comprehensive analysis of MAPK13/inhibitor complexes of widely varied potency•Inhibitors of nanomolar IC50 bind in DFG-out mode; micromolar IC50 bind DFG-in.•Nanomolar IC50 correlates with longer dissociation half-lives.•Binding thermodynamics of inhibitors correlates with potency.•The data provide a guide for designing high potency inhibitors to MAPK13.